2014
DOI: 10.1002/jib.134
|View full text |Cite
|
Sign up to set email alerts
|

HPLC and GC-MS analyses of organic acids, carbohydrates, amino acids and volatile aromatic compounds in some varieties of rice beer from northeast India

Abstract: Rice beer samples of nine different varieties from four states of northeast India were studied for the content of organic acids, carbohydrates and amino acids by high-performance liquid chromatography. The aromatic compounds were detected by gas chromatography-mass spectrometry method. The analysis evinced a wide variation in content of the major organic acids. Lactic acid was found in high concentration in all of the samples, while the other organic acids were present in variable amounts. Among the carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 33 publications
(45 reference statements)
2
39
0
Order By: Relevance
“…Concentrations were calculated by the comparison of integrals from unique assigned peaks from each component molecule ( Table 2 shows the assignment), knowing the number of protons associated with each component signal (N), the number of mass of maleic acid in solution (10 mg added from a 100 mg/mL stock solution) and the volume of sample (175 µL). Concentrations of major organic compounds are listed in Table 3 and appear to be in reasonable agreement with previously published data [12,13]. Quantitative NMR has been demonstrated previously to be a precise method with variations of less than 1.0% [14,15].…”
Section: Nmr Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Concentrations were calculated by the comparison of integrals from unique assigned peaks from each component molecule ( Table 2 shows the assignment), knowing the number of protons associated with each component signal (N), the number of mass of maleic acid in solution (10 mg added from a 100 mg/mL stock solution) and the volume of sample (175 µL). Concentrations of major organic compounds are listed in Table 3 and appear to be in reasonable agreement with previously published data [12,13]. Quantitative NMR has been demonstrated previously to be a precise method with variations of less than 1.0% [14,15].…”
Section: Nmr Resultssupporting
confidence: 85%
“…Several compounds were found to be below the detection limit for the method. Further optimization of the method may be possible to produce lower detection, however, the values determined are in a typical range for beer samples [12,13]. The highest isoamyl acetate values were detected in samples 1 and 9, which were both characterized as Belgian style ales.…”
Section: Nmr Resultsmentioning
confidence: 91%
“…Despite the evolving trend of using bacteria for ethanol production, yeast is still the primary choice for fermentation (2). The production of wine from several rice varieties has been reported (3,4), however, literature related to the production of wine from black pigmented rice is scanty. Several studies have suggested an association between intake of black pigmented rice and health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The colour of the black rice wine sample was measured using Hunter Lab Color Quest (Ultrascan Vis, HunterLab, USA) in terms of L * a * b *. The L * a * b *, or CIELab, colour space is an international standard for colour measurements, adopted by the Commission Internationale d'Eclairage in 1976 .…”
Section: Methodsmentioning
confidence: 99%